2014
DOI: 10.1597/12-135
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Orofacial Clefts in Nigeria

Abstract: Orofacial clefts (OFC) are the most common malformations of the head and neck. In Africa, OFC is under-ascertained with little or no surveillance system in most parts for clefts and other birth defects. A Nigerian craniofacial anomalies study “NigeriaCRAN” was established in 2006 to support cleft research specifically for epidemiological studies, treatment outcomes and; studies into etiology and prevention. We pooled data from seven of the largest Smile Train treatment centers in the six geopolitical zones in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
61
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 34 publications
14
61
2
Order By: Relevance
“…The distribution of the cleft types which is done for all operated cleft patients (18073) during the study period is: cleft lip only (CLO = 12831, cleft lip and palate (CLP=4632), and cleft palate only (CPO = 541). The number of isolated cleft palate in this study (3%) is low similar to other African studies (15, 16,11), It is also more common in males similar to the study done by Conway et al (16). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The distribution of the cleft types which is done for all operated cleft patients (18073) during the study period is: cleft lip only (CLO = 12831, cleft lip and palate (CLP=4632), and cleft palate only (CPO = 541). The number of isolated cleft palate in this study (3%) is low similar to other African studies (15, 16,11), It is also more common in males similar to the study done by Conway et al (16). …”
Section: Discussionsupporting
confidence: 90%
“…Iregbulem (1982) reported a prevalence of 0.3/1000 in the Eastern part of Nigeria (10). Butali et al (2014) reported a countrywide prevalence of 0.5/1000 (11). The incidence and prevalence of these anomalies in Ethiopia are not known and there are only two published reports about these anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we found a higher frequency of associated congenital malformations, whereas African studies found lower frequencies between 4 and10.5% [18, 19]. Our result, however, was lower than in some reports from the Middle East and Asia where [20] found a frequency of 43.3% in Jordan, [2] reported 14.8% in India; [3, 4] reported 17.8 and 21.6% in Iran, respectively.…”
Section: Discussioncontrasting
confidence: 82%
“…The worldwide average birth prevalence of all orofacial clefts is 9.92 per 10,000 (close to one per 1,000), but there is substantial variation among populations 7 . In general, East Asian and Native American populations have substantially higher birth prevalence rates than do European and South Asian populations, while African ancestry populations have lower birth prevalence rates 810 .…”
Section: Introductionmentioning
confidence: 97%